2012
DOI: 10.1371/journal.pone.0036396
|View full text |Cite
|
Sign up to set email alerts
|

Hiding from the Moonlight: Luminosity and Temperature Affect Activity of Asian Nocturnal Primates in a Highly Seasonal Forest

Abstract: The effect of moonlight and temperature on activity of slow lorises was previously little known and this knowledge might be useful for understanding many aspects of their behavioural ecology, and developing strategies to monitor and protect populations. In this study we aimed to determine if the activity of the pygmy loris (Nycticebus pygmaeus) is affected by ambient temperature and/or moonlight in a mixed deciduous forest. We radio-collared five females and five males in the Seima Protection Forest, Cambodia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(39 citation statements)
references
References 60 publications
2
35
2
Order By: Relevance
“…A higher risk of heat loss could be another reason for possums to cross the bridge less on windy nights (McCafferty et al 2011); however, this is unlikely to be the case given that the number of crossings actually increased on colder nights, contrary to our expectation. It seems that heat loss is not as big problem for P. occidentalis as for other arboreal mammals studied by Laurance (1990), Starr et al (2012), and Rode-Margono and Nekaris (2014). These researchers studied species in tropical regions such as Northern Queensland, Cambodia, and West Java, and their study species might have been more susceptible or less adapted to cold conditions compared to P. occidentalis.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A higher risk of heat loss could be another reason for possums to cross the bridge less on windy nights (McCafferty et al 2011); however, this is unlikely to be the case given that the number of crossings actually increased on colder nights, contrary to our expectation. It seems that heat loss is not as big problem for P. occidentalis as for other arboreal mammals studied by Laurance (1990), Starr et al (2012), and Rode-Margono and Nekaris (2014). These researchers studied species in tropical regions such as Northern Queensland, Cambodia, and West Java, and their study species might have been more susceptible or less adapted to cold conditions compared to P. occidentalis.…”
Section: Discussionmentioning
confidence: 88%
“…Other arboreal folivorous species have been observed to be less active on well lit nights with low temperatures, presumably to avoid the risk of predation and heat loss (Laurance 1990, Starr et al 2012, RodeMargono and Nekaris 2014. Greater wind speed also decreased the number of common brushtail possums (Trichosurus vulpecula) observed in open pasture (Paterson 1993).…”
Section: Introductionmentioning
confidence: 99%
“…lunar luminance or environmental variables) can override endogenous circadian rhythms by inhibiting or enhancing activity (Erkert 1989;Chiesa et al 2010). Decreasing activity with increasing lunar illumination (lunarphobia) is common in many mammals (Penteriani et al 2011;Prugh and Golden 2014), including carnivores (Halle 2000;Packer et al 2011), bats (Erkert 1974(Erkert , 1976Saldaña-Vázquez and Munguía-Rosas 2013), rodents (O'Farrell 1974;Kaufman and Kaufman 1982;Corsini et al 1995;Upham and Hafner 2013), and primates (Bearder et al 2006;Starr et al 2012;Rode-Margono and Nekaris 2014). Conversely, relatively few mammals display lunarphilia, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Trent et al (1977), in a study of captive animals, reported greater slow lorises to be lunar phobic. Starr et al (2012) reported that wild pygmy slow lorises were clearly lunar phobic during the dry cool season, but showed lunar neutrality during the colder wet season. For wild slender lorises Loris tardigradus, Bearder et al (2002) noted that they called more frequently during moonlit nights and that they increased foraging and travelling during full moon, suggesting that slender lorises are lunar philic.…”
Section: Surveying At Nightmentioning
confidence: 99%
“…speed at which surveys are conducted) both strongly influencee detectability, again possibly more so during the night than in the day. As noted by Starr et al (2012) the sensory world of the forest at night has strongly influenced the behaviour and physiology of nocturnal mammals. In the absence of visual sensory cues, the activity patterns of many nocturnal mammals are affected by the intensity of nocturnal illumination.…”
Section: Introductionmentioning
confidence: 99%